Haití. Réalisations 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
IICA participated in the implementation of the digital transformation project for agriculture with Agriterra and the funds from the International Fund for Agricultural Development (IFAD). The project aimed to mitigate the impact of COVID-19 and the subsequent crisis by developing digital solutions that allow better internal management and access to markets and financing. The IICA provided virtual training to members of producer organizations on digital marketing and digital applications for commercialization. The IICA also developed the AgriExt mobile application, which aims to improve interaction and information exchange between extension agents and farmers, and facilitate access to priority information to address farmers' problems. Additionally, the IICA strengthened the capacity of agricultural goods and services providers through training sessions and consultations to increase the productivity of small farmers in certain departments of Haiti.